2020
DOI: 10.14710/politika.11.2.2020.219-238
|View full text |Cite
|
Sign up to set email alerts
|

Sikap dan Perilaku Warga terhadap Kebijakan Penanganan Wabah Covid-19

Abstract: Sebuah kebijakan publik akan efektif jika publik mendukungnya. Hal yang sama berlaku dalam konteks wabah  Covid-19. Sejauh ini belum ada studi tentang kebijakan pemerintah Indonesia, khususnya terkait Pembatasan Sosial Berskala Besar (PSBB), dan kepatuhan warga terhadapnya. Tulisan ini mengisi kekosongan tersebut dengan bertumpu pada hasil penelitian opini publik nasional tentang sikap dan perilaku publik terkait PSBB dan protokol kesehatan. Hasilnya adalah perilaku dan sikap pada kebijakan tersebut berhubunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 8 publications
0
11
1
7
Order By: Relevance
“…This affects the trust and participation of citizens. Several studies have also shown a correlation between government capacity and community participation (Kuipers et al, 2020;Ladiqi, 2020;Mujani, 2020;Mujani & Irvani, 2020). For more than six months, the author observed that the participation of the citizens of Bandung City in the form of non-compliance increased.…”
Section: Results and Discussion Political Noise In Crisismentioning
confidence: 92%
“…This affects the trust and participation of citizens. Several studies have also shown a correlation between government capacity and community participation (Kuipers et al, 2020;Ladiqi, 2020;Mujani, 2020;Mujani & Irvani, 2020). For more than six months, the author observed that the participation of the citizens of Bandung City in the form of non-compliance increased.…”
Section: Results and Discussion Political Noise In Crisismentioning
confidence: 92%
“…Seseorang yang merasakan keadaan ekonominya sekarang lebih baik maka ia cenderung akan bersikap dan berperilaku positif terhadap setiap kebijakan yang dilahirkan oleh pemerintah. 11 Terhadap kondisi pandemi yang tidak terduga seperti terjadinya wabah Covid-19 ini, maka berbagai permasalahan baru muncul dan harus segera dicarikan jalan penyelesaiannya. Disinilah kebijakan pemerintah hadir untuk menyelesaikan permasalahan yang ada secara cepat.…”
Section: Hasil Penelitian Dan Pembahasan Peranan Kebijakan Pemerintah Ditengah Kondisi Yang Gentingunclassified
“…The attitudes and behaviour of citizens towards the COVID-19 Outbreak Management Policy are closely related to the background of political behaviour, belief in the government's ability to handle COVID-19, employment status, income, education, religion, and gender (Kuipers et al 2020;Mujani and Irvani, 2020). According to this study, the number of voters for the Joko Widodo-Ma'ruf Amin pair compared to the Prabowo Subianto-Sandiaga Uno pair in 2019 agreed with the PSBB gender (Kuipers et al 2020, 9;Mujani and Irvani 2020, 233-234).…”
Section: Psbb Policy and Various Reactionsmentioning
confidence: 99%
“…According to this study, the number of voters for the Joko Widodo-Ma'ruf Amin pair compared to the Prabowo Subianto-Sandiaga Uno pair in 2019 agreed with the PSBB gender (Kuipers et al 2020, 9;Mujani and Irvani 2020, 233-234). The study of Mujani and Irvani (2020) and Kuipers et al (2020) which is based on the results of a survey by Saiful Mujani Research and Consulting (SMRC) on public attitudes and behaviour related to the COVID-19 outbreak, April 23-26, 2020, seems to provide an analytical tool to answer why fatwas or views of religious figures regarding restrictions on salat berjamaah are partially neglected people at the grassroots. For example, Pabbajah et al (2020) shows that these fatwas not followed by some people and are considered a symptom of the de-authorization of the ulama in preventing the CIVID-19 outbreak (Pabbajah et al 2020, 267).…”
Section: Psbb Policy and Various Reactionsmentioning
confidence: 99%